Knowledge, Attitudes and Practices on Community with Dengue Haemorrhagic Fever in Mataram, West Nusa Tenggara - Nur Alvira Pascawati; Tri Baskoro Tunggul Satoto; Tri Wibawa; Roger Frutos; Sylvie Maguin; I Kadek; Ali Wardana (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
Dengue Haemorrhagic Fever (DHF) is a major health problem in Mataram. Even though there have been many prevention efforts, the rates of morbidity and mortality tend to increase. This condition shows that the indicators of Knowledge, Attitude, and Practice (KAP) about DHF in the community are still low. This study aims to prove the factors KAP in the community with DHF in Mataram City. The research conducted in October-November 2018 used a case-control study. The sampling technique used proportional stratified random sampling The KAP data were collected by interview using questionnaires and observation using a structured checklist. Data analysis used a simple and multiple logistic regression test (α = 5%). Factors related to DHF transmission in Mataram are the communities' habit of raising livestock, does not have a temporary landfill, low knowledge about DHF, lots of garbage around the house and the determinant factor is a routine mobilization to endemic areas (OR = 17.019). DHF reduction in Mataram City can be carried out through integrated cross-sectoral vector control activities as through waste management; build livestock pens according to health standards and provide education, especially for community living in endemic areas.